(35) Integrated Methodology for Energy planning in Egypt المنهجية المتكاملة لتخطيط الطاقة في مصر - Emad El Sharkawi (The Institute of National Planning, 2018)
Planning for an adequate supply of energy has always been an important component of national planning in Egypt. The dramatic fluctuation of oil prices and the changes in the future energy supply and demand pattern call for a comprehensive approach to energy planning.